2020
DOI: 10.1097/hjh.0000000000002295
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A pathway: from pathogenic molecule to renal disease

Abstract: Background: Chromogranin A (CHGA) is an index granin protein critical for biogenesis and exocytotic release of catecholamine storage granules. It is elevated in plasma of patients with sympathetic over-activity and kidney dysfunction. Several CHGA polymorphisms are associated with hypertensive kidney disease. Previously, we unraveled the molecular mechanism by which CHGA expression is regulated in African Americans carrying a genetic variation associated with hypertensive chronic kidney disease (CKD).Method: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Consistent with previous studies, we found EGLN3 was increased in short time, while reduced in long time after hypoxic treatment. CHGA is a member of the chromogranin/secretogranin family of neuroendocrine secretory proteins [ 39 ]. It is found in secretory vesicles of neurons and endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we found EGLN3 was increased in short time, while reduced in long time after hypoxic treatment. CHGA is a member of the chromogranin/secretogranin family of neuroendocrine secretory proteins [ 39 ]. It is found in secretory vesicles of neurons and endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, serum CgA increases in renal failure more than creatinine and the other studied low-MW proteins, β2-MG (β2 microglobulin) and TATI (tumor-associated trypsin inhibitor) [ 12 ]. In animal experiments, an inverse correlation suggested a decrease in GFR with increasing plasma CgA concentration [ 30 ]. The study by Chen et al suggests CgA-stimulation of endothelial cell exocytosis of endothelin as a possible mechanism for regulation of renal function in health and disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these four biomarkers, CHGA has been reported to have a clear relationship with MDD [ 22 , 23 ]. CHGA is a protein-coding gene [ 23 ] and a member of the chromogranin/secretogranin family of neuroendocrine secretory proteins [ 24 ], which may influence the exocytotic release of neurotransmitters, including 5-hydroxytryptamine and dopamine—neurotransmitters that are involved in the sleep-wake cycle as well as implicated in depression. One study that investigated sectional CHGA levels in 40 male university students indicated an inverse association between salivary levels of CgA and the intensity of depressive symptoms [ 25 ].…”
Section: Discussionmentioning
confidence: 99%